2016
DOI: 10.5530/ijopp.9.4.3
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Anti-hyperglycemic Drug Utilization Patterns and Adherence to AACE/ACE 2015 Guidelines in South Indian Tertiary Care Teaching Hospital

Abstract: Aim:To compare adherence to American Association of Clinical Endocrinologists/American College of Endocrinology (AACE/ACE) 2015 guidelines for diabetes care in a tertiary care teaching hospital in India. Method: In this prospective observational study, 415 prescriptions of type 2 diabetes mellitus (T2DM) patients were collected in Dr. Pinnamaneni Siddhartha Institute of Medical Sciences (PSIMS) hospital from January 2015 and June 2015. Medication adherence to AACE/ACE guidelines was assessed based on glycated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In a study at Vijayawada, Hypertension (HTN) (39.8%, male; 39.7%, female) is the most predominant co-morbidity, followed by patients with both HTN and cardio vascular diseases (9.4%, male; 9.8%, female). 8 In a prospective cross-sectional study at UAE most common comorbidities associated with type 2 diabetes was found to be Hypertension (83.40%) followed by obesity (90.49%) and dyslipidemia (93.43%). 9 In a study conducted at Bankura Medical College 74.0% were suffering from associated comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…In a study at Vijayawada, Hypertension (HTN) (39.8%, male; 39.7%, female) is the most predominant co-morbidity, followed by patients with both HTN and cardio vascular diseases (9.4%, male; 9.8%, female). 8 In a prospective cross-sectional study at UAE most common comorbidities associated with type 2 diabetes was found to be Hypertension (83.40%) followed by obesity (90.49%) and dyslipidemia (93.43%). 9 In a study conducted at Bankura Medical College 74.0% were suffering from associated comorbidities.…”
Section: Discussionmentioning
confidence: 97%